The Linkage Between Palm Oil Producer Prices and Economic Factors - Dedi Budiman Hakim; Adi Hadianto; Syamsul Hidayat Pasaribu; Widyastutik Widyastutik; Iwan Hermawan; Lilis Hoeriyah; Triana Anggraenie; Deviyantini; Fikri Aldi Dwi Putro (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Despite being the world's dominant CPO producer (contributing approximately 58 percent of global output in 2023), Indonesia structurally operates as a price taker. CPO pricing consistently refers to international exchanges (BMD and Rotterdam) because domestic futures exchanges (BBJ/ICDX) are suboptimal due to the voluntary and inconsistent implementation of Bappebti Regulation No. 7/2023, which leads to low liquidity and transaction fragmentation.Purpose: This study addresses the underexplored gap by analyzing how global market integration and domestic price factors jointly determine Indonesian CPO forward prices and their causal relationship with Malaysia and Rotterdam prices.Design/Methodology/Approach: The study utilized monthly data from May 2010 to January 2025, as this period captures major global economic events, policy changes, and market fluctuations that significantly influenced Indonesia’s CPO price dynamics. The econometric models employed include the Error Correction Model (ECM) and Vector Error Correction Model (VECM), supported by Granger Causality, Impulse Response Function (IRF), and Variance Decomposition (VD) analyses. Findings/Results: The Indonesian CPO forward price is positively and significantly influenced by both Malaysian and Rotterdam CPO prices. Causality analysis confirms the price-taker status, identifying a one-way causal relationship in which Malaysia and Rotterdam predict Indonesian price changes. Dynamically, Indonesian prices exhibit a sensitive adjustment, responding positively to global shocks only briefly before they turn negative. The Rotterdam CPO price is the most significant external contributor to the Indonesian price variance over the long term.Conclusion: The findings confirm the persistent structural dependence of Indonesian CPO prices on international benchmarks. This underscores the urgent need for decisive policy intervention specifically, the mandatory domestic CPO trading policy through the Indonesia Commodity and Derivatives Exchange (ICDX) to foster stronger market liquidity, thereby enabling Indonesia to leverage its global production dominance and effectively transition into a global price reference for CPO.Originality/Value (State of the Art): This study provides a cutting-edge empirical contribution by combining ECM–VECM, IRF, and VD models to measure the structural relationships among major CPO markets. Unlike previous studies that typically examine price transmission using only single-equation models or limited time frames, this study incorporates a longer dataset and a comprehensive multivariate framework to capture both short-run adjustments and long-run causality. This study fills a key gap in the literature regarding the persistent structural dependence of Indonesian CPO prices on international benchmarks and highlights the urgency of strengthening Indonesia's role in the global pricing mechanism. Keywords: crude palm oil, futures exchange, price integration, causality analysis, econometric models